Pengaruh Metode Pembelajaran Mind Mapping Terhadap Hasil Belajar Peserta Didik Pada Materi Mitigasi Bencana Alam - Sucahyanto, Sucahyanto; Lestrainingsih, Dwi Sukanti; Apriani, Sarah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of applying the Mind Mapping learning method to the learning outcomes of class X students at SMAN 42 Jakarta. This research started from the results of students' daily tests on Geography which were not optimal. This study aims to determine the effect of applying the Mind Mapping learning method to the learning outcomes of class X students at SMAN 42 Jakarta. This research started from the results of students' daily tests on Geography which were not optimal. This study uses a descriptive quantitative method with an experimental approach. The design used in this research is quasi-experimental. This research was conducted at SMAN 42 Jakarta using class X-7 as the research sample with a total of 32 students. This research took place for 3 weeks or 3 meetings according to the hours of geography subjects. The data obtained comes from the value of the N-Gain Score and the value of the hypothesis test. From the results of calculating the average value before being given treatment (preliminary test) with an average value obtained is 39.70 and after being given treatment (final test) with an average value obtained is 72.45 there is a change where the average value is average difference of 32.75. From the results table of the N-Gain test in the experimental class it can be concluded that the Mind Mapping learning method with interpretation is quite effective, because the average value obtained is 70.21% where this value can be said to be quite effective because looking at the test criteria which is 56% - 75% is said to be quite effective. And the results of the proposed hypothesis obtained Sig. equal to 0.00 ≤ 0.05 means that there is influence from variable X with variable Y, namely the application of the Mind Mapping learning method has an influence on student learning outcomes in the natural disaster mitigation sub-material in class X SMAN 42 Jakarta. However, students have not mastered and understood Mind Mapping well, students are only able to understand Mind Mapping as a way of writing their ideas or ideas in written form or a summary that they understand to be used as a way of writing to understand learning material.